Two‐level scheduling of an active power distribution network by considering demand response program and uncertainties - Alireza Rahnama; Abdolmajid Dejamkhooy; Hossein Shayeghi (Engineering Reports, 2023)
Abstract This study investigates a hierarchical approach for modeling the mutual impacts of distribution network (DN) decisions and microgrids in a multi‐microgrid system under the cover of a two‐level problem. Due to the conflicting interests of decision‐makers in an active DN, the optimization problem has a hierarchical structure, with distribution companies (Discos) at the top attempting to maximize profits and microgrids at the bottom attempting to reduce costs. This study examines the relationship between the unpredictability of renewable energy sources and power demand. In this mechanism, the influence of the demand response program (DRP) is also considered an important aspect of intelligent systems. The two‐level nonlinear optimization problem has been transformed to a one‐level linear problem using dual theory and KKT conditions. According to the findings of the studies, even though cost reduction is the sole objective of scheduling in centralized mode, applying DRP to the system results in a 16% reduction in overall costs for the two‐level scheduling method, and a 22% reduction in daily costs when compared to two‐level scheduling without DRP.